“Zollywood, Zimbavision and Zimbowood?”: In search of new paradigms for Zimbabwe's film industry - Rwafa, Urther (Unisa Press, 2016)
This paper problematises three concepts: Zollywood, Zimbavision and Zimbowood. The re-evaluation of Zimbabwe’s film industry that this article is going to carry out is partly influenced by ongoing public debate focused on identifying Zimbabwe’s film industry through nomenclature. However, it is argued in this paper that the Zimbabwean film industry needs more than naming. It also needs restructuring so that the industry can begin to address filmic issues critically and animatedly with Zimbabweans and international audiences through the introduction of new models, themes and perspectives. I therefore advocate for a paradigm shift - which is a radical relook at the conditions of film production, distribution and marketing of Zimbabwe’s film images. What is also central in this paper is the search for research methodologies and that injects “newness”, agency and vibrancy into Zimbabwe’s film industry. In addition, 1 challenge academics, filmmakers and audiences to debate the conditions that restrict or censor Zimbabwean film images from effectively penetrating the public domain.